Growth Of Zno Nanorods Using Hydrothermal And Modified Chemical Bath Deposition For Device Applications - M. Mohammad, Sabah (2017)
Zinc oxide (zno) is applications in high efficiency electronic and optoelectronic devices. The present study follows two objectives. First, synthesis of vertical and inclined well-aligned zno nanorods (nrs) on a nylon substrate via the hydrothermal method, and subsequently fabricate the highly flexible low-cost ultraviolet photodiodes (uv-pds) and hydrogen (h2) gas sensor devices. Pre-heat treatment of zno seeds/substrate at 180°c with varying duration (0.5-6 h) shows important changes. Morphological observations revealed the formation of aligned hexagonal-like shaped nanorods when the diameter, length (aspect ratio), surface area and density increase with increasing heat treatment time. The x-ray diffraction analysis confirms the formation of wurtzite zno phase with a preferred orientation along (002) direction and enhanced crystallinity. Photoluminescence spectra exhibited a strong and sharp ultraviolet (uv) near band edge emission peak that was higher than that of the broad peak. Temperature and duration to produce uniform zno seeds was 180°c for 3 h.